Peranan Sistem Penerimaan Dan Pengeluaran Kas Dan Setara Kas Terhadap Efektivitas Pengelolaan Kas Pada Koperasi Simpan Pinjam Sejahtera Bersama - Rosita, Siti Ita; Fahmi, Arief; Istichaerani, Istichaerani (Jurnal Ilmiah Akuntansi Kesatuan, 2015)
This paper is aimed at comparing cash in and cash out system within a company's cash management system.The object took place at Koperasi Simpan Pinjam Sejahtera Bersama, in Bogor. The research resulted that Koperasi Simpan Pinjam Sejahtera Bersama already has afixed and computerized cash procedure, to maintain functional cash activities. The firm also applies intemal audit procedures for security reasons. It is also revealed that the finn a good cash system for encouraging efective and smooth operating. However, there is an aÂ±owledgement ofthe necessityfor an on time daily transaction report. Keywords : cash in and cash out, cash management